Biology Education and Research in a Changing Planet
XI, 225 p. 47 illus., 18 illus. in color.
Keywords: This book presents selected conference proceedings from the 25th Biennial Asian Association for Biology Education Conference. It clarifies the differences between the structure of biology education for educators and researchers. It solves open problems by creating a bridge between biological research and its application in education and the sustainable development of communities. The book’s first topic is Biology Education in an X, Y, Z World, which provides ideas for how biology can be taught in innovative ways. The second topic, The Endangered Planet – How can Biology Education Help? discusses how humans depend on other species for survival and how they have the power to cause or to prevent extinctions. The third and final topic, Research in Biology, encompasses the growing wealth of biological information resulting from scientific research, especially in universities. Educators can use these findings to enhance their teaching.